A study of detection of diarrhoea associated human rotavirus and co-infection with diarrhoea genic pathogens in childhood stool specimen by using ELISA and RT-PCR in a tertiary care hospital at Indore, Madhya Pradesh - Rajput, Madhurendra Singh; Rawat, Jagat Bahadur; Vashishtha, Ankur; Panwar, Gautam; Sharma, Prigya (International Journal of Research in Medical Sciences, 2024)
Background: Childhood diarrhoea mainly caused by Group A Rotavirus, is a major global health issue, especially for children under five. In India, RVA-induced diarrhoea causes numerous deaths, hospitalizations, and outpatient visits annually. Vaccination is crucial in preventing RVA, with WHO-approved oral vaccines significantly reducing global mortality and morbidity. However, challenges persist in implementing vaccines in regions like sub-Saharan Africa due to factors like malnutrition and unsanitary conditions. Despite this, since 2009, low-income countries have seen a decline in RVA-related illness. Methods: Over 18 months, from January 2021 to June 2022, a study at the Post Grad Dept. of Microbiology, Index Medical College, Hospital and Research Centre in Indore, MP, involved 250 children under five with acute gastroenteritis. Ethical clearance and parental consent were obtained. Data included demographic, antenatal, diarrhoea l symptoms, feeding, hygiene, physical exams, and stool analysis. Results: 250 children under five were screened for Rotavirus. 60 tested positive, mostly in 6–12-month-olds during cooler months in urban areas. 80% were from low socioeconomic backgrounds. Exclusive breastfeeding linked to lower incidence. Vomiting and severe dehydration more frequent in positive cases. ELISA and ICG methods equally effective. Conclusions: Childhood diarrhoea, primarily caused by Rotavirus, remains a leading cause of under-five deaths, totalling 600,000 annually. Among 250 children studied, 60 tested positive for Rotavirus, especially among males aged 7-12 months, with infections peaking in cooler months. Both ELISA and ICG were equally effective in detection. Treatment primarily involves oral rehydration with low osmolarity ORS. Predominant strains were G1 P (8) and G2 P (4). Global endorsement of rotavirus vaccines like Rotarix and Rotateq, with Rotavac showing promise in India, signals progress in fighting rotavirus, potentially improving public health via inclusion in state immunization programs.